AKIBAT HUKUM PENOLAKAN AUTOPSI OLELH KELLUARGA DALAM KASUS KEMATIAN TIDAK WAJAR (STUDI KASUS PUTUSAN PERKARA NOMOR: 629/PID.B/2021/PN.SEI RAMPAH) - Wijaya, Radar; Soekorini, Noenik; Nasoetion, Dedi Wardana; Taufik, Moh. (Gapenas Publisher, 2025)
Forensic autopsies play a crucial role in criminal proceedings because they can reveal the cause of death scientifically and objectively. However, the practice in Indonesia still faces a dilemma when the victim's family refuses to allow an autopsy to be performed. This situation poses a serious problem, given that without an autopsy, the causal relationship between the perpetrator's actions and the victim's death is difficult to prove legally. This study stems from the urgency to understand the position of autopsy in criminal law and to examine the legal consequences that arise when families refuse to allow it to be performed. The main questions to be answered are how the refusal of an autopsy affects the quality of criminal evidence and what the legal consequences are for court decisions. The research method used is normative juridical with a case approach, through a study of legislation, doctrine, and court decisions, particularly the Sei Rampah District Court Decision Number 629/Pid.B/2021/PN.Sei Rampah. Primary legal materials were obtained from the Criminal Code, Criminal Procedure Code, and Health Law, while secondary legal materials were obtained from academic literature and previous research. The analysis was conducted qualitatively, focusing on the relationship between legal norms, judicial practice, and the implications of refusing an autopsy. The results of the study show that the refusal of an autopsy by the victim's family has a direct impact on the weakness of criminal evidence. Judges cannot scientifically determine the cause of death, so defendants are often only sentenced on lesser subsidiary charges. These findings confirm a legal loophole in the Criminal Procedure Code, which only regulates notification to families without regulating the mechanism in the event of refusal. The conclusion of this study confirms that existing regulations are insufficient to address the dilemma between the rights of the victim's family and the public interest in upholding justice. Therefore, more explicit updates to criminal procedure law are needed, as well as legal communication strategies that can increase public understanding of the urgency of autopsies. Further research is recommended to examine the ethical and social dimensions in greater depth so that the solutions offered are more comprehensive.